Anaphore associative et relations de cohérence : une expression particulière de la relation Assertion-Indice - Mathilde Salles (Discours)
Anaphoric relations and lexical relations can guide the hearer or reader in the recognition of coherence relations. These two kinds of markers occur with associative anaphora. Are they complementary? What part do they take in the interpretation of coherence relations? In this paper, I suggest that this anaphoric way to introduce some lexical relations (in particular part-whole relations) affects the argumentative nature of coherence relations and explains the affinity we can observe between associative anaphora and the relation Claim-Evidence (Cornish, 2009a and b). A comparison with possessive anaphora, a competitive way of introducing part-whole relations, emphasizes that this effect is peculiar to associative anaphora and not due to the use of the lexical relation itself.